Establishing an untargeted-to-MRM liquid chromatography–mass spectrometry method for discriminating reconstituted milk from ultra-high temperature milk. (1st February 2021) - Tan, Dongfei; Zhang, Xia; Su, Meicheng; Jia, Man; Zhu, Dan; Kebede, Biniam; Wu, Huaxing; Chen, Gang
Highlights: Metabolites in UHT and reconstituted milk were compared. An untargeted metabolomics approach was used to differentiate the two types of milk. Differential biomarkers were classified by hierarchical clustering analysis. The candidate biomarkers can be categorized as peptides, lipids, and nucleic acids. Milk powder processing causes nutritional loss, especially for peptides and lipids. Abstract: The counterfeit use of reconstituted milk to simulate fresh milk in some countries is largely driven by profiteering; hence, establishing a robust market-surveillance method is an important objective. In this study, an untargeted metabolomics approach that uses ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC–Q-TOF-MS) was established to discover biomarkers that can be used to classify UHT and reconstituted milk. Furthermore, 36 positive- and 24 negative-ionization mode features were selected as candidate markers to establish a UPLC–tandem mass spectrometry (UPLC–MS/MS) multiple reaction monitoring (MRM) method. The support vector machine (SVM) method was used to process the responses of the selected potential markers, and 100% classifiability was observed. The marker metabolites could be divided into three categories by hierarchical clustering analysis: peptides, lipids, and nucleic acids. The results suggest that the untargeted-to-MRM metabolomics method is an effective tool for distinguishing between UHT and reconstituted milk.